Ultra-mini-percutaneous nephrolithotomy in pediatric nephrolithiasis: Both low pressure and high efficiency. Issue 5 (October 2015) - Dede, Onur; Sancaktutar, Ahmet Ali; Dağguli, Mansur; Utangaç, Mazhar; Baş, Okan; Penbegul, Necmettin
Summary: Introduction: The management of urolithiasis in children differs from adults because of anatomic and metabolic abnormalities. At present, various minimally invasive and invasive treatment strategies have been recommended to treat urinary tract Stones, including shock wave lithotripsy (SWL), standard percutaneous nephrolithotomy (PNL), mini-PNL, retrograde intrarenal surgery (RIRS), micro-PNL, and a new technique termed ultra-mini PNL (UMP). UMP is a new method for the treatment of kidney stones. The main difference between UMP and standard PNL or mini-PNL lies in the small access sheath and in its design. A 9.5F pediatric compact cystoscope was used (Figure). A major advantage of UMP is that it provides similar stone-free rates when compared with standard PNL, with lower intrarenal pressure than micro-PNL. Objective: The aim of the study was to determine the applicability and safety of UMP in the treatment of pediatric kidney stones. Patients and methods: We retrospectively reviewed the files of 39 kidney stones in children who had undergone UMP between May 2011 and October 2014. The indications for UMP included stones resistant to SWL, stones requiring repeated sessions of SWL, and stones size larger than 20 mm. Results: The study included 17 females and 22 males, with a mean age of 5.8 ± 4.6 years. The mean hemoglobin loss was 0.9 ± 0.6 mg/dL and none of the patients required a blood transfusion. The complication rate of the PNL procedure was 15.3% ( n = 6). Complete clearance was achieved in 32 patients (82%) with UMP monotherapy, which increased to 34% (87.1%) 4 weeks after the operation. Discussion: Management of urolithiasis necessitates a balance between stone clearance and morbidity related to the procedure. SWL often leads to persistent residual stones. The developing RIRS can minimize the risks associated with bleeding and visceral injury, but sometimes the abnormal pelvicaliceal anatomy and poor imaging of the flexible ureteroscopy may impact its success rate and applications. It has been reported that PNL can be performed safely and effectively to achieve a higher stone-free rate; however, it has serious complications such as bleeding that requires blood transfusion in 11–14% of the cases with increased risk of kidney loss. The recent development of smaller sheaths allows tract formation with minimal damage to the renal parenchyma, thereby reducing procedure-related morbidity without diminishing its therapeutic efficacy. Conclusion: The most important advantage of this surgical technique that has been developed is similar stone-free rates to standard PNL and lower intrarenal pressure than micro-PNL. Our experience supports that UMP is safe and effective for the management of renal stones in children. Figure 9.5F nephroscope (pediatric cystoscope) and 6F–12F dilator set.